Elaboration of carbonated beverages with sucralose from eggplant - Loyola Lopez, Nelson; Acuña Carrasco, Carlos; Arenas Bravo, Leonardo; Arriola Herrera, Mariela (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The eggplant (Solanum melongena L.) it is edible fruit plant, rich in vitamins, minerals and phenolic compounds, so its consumption brings health benefits. The objective of this work was to evaluate the quality nutritional, sensory and hygiene assessment of the beverage based on eggplant juice with CO2 injection. This study had four treatments; Treatment T0 Eggplant juice (330 mL), T1 Eggplant juice (330 mL) + CO2 (1,94 g) T2 Eggplant juice (330 mL) + CO2 (1,94 g)+ Benzoate (1 g), T3 Eggplant juice (330 mL) + CO2 (1,94 g) + Sucralose (1 g). Evaluations were carried out at 24 hours, 30 and 60 days of storage (0°C and 95 % RH) and, at each of these moments, the acidity content, pH, reducing sugars, soluble solids and Vitamin C were determined. Sensorial evaluation measure were; color, flavor, texture, aroma and also acceptability and appearance. In regards to microbiological analysis, total coliforms were measured at 24 hours after the beverage was made. There was significant difference in the results of appearances between beverages elaborated with treatments T3 in relation with T0, T1 and T2at 24 hours and 30 days of storage. Because of beverage with treatment T3 had got better acceptability by the panelists, mainly at 30 days of storage. Therefore, beverages elaborated with treatments T0 at 24 hours and 30 days of storage had lower appearance and acceptability. The vitamin C content showed a 25 mg (23 mg standard) in the beverages elaborated with treatments T3. The pasteurization process allowed the absence of total coliform in the beverages elaborated and also the good manufacture practices obtained an innocuous product to be consume.Keywords: microbiological analysis, nutritional analysis, sensorial analysis, Solanum melongena L.